The Effect Of Physical Facilities Quality On Tourist Satisfaction At Taman Ayun Temple Attraction By Vitruvius Theory As A Moderating Variable - Sari, Retno Juwita; Winston, Tasya; Prawira, Putu Agung Surya; Pracintya, Ida Ayu Etsa (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
Tourism activities should be able to be done by all age groups, including the elderly. However, many tourist attractions are not friendly to elderly tourists. Starting from attractions, access and accommodation provided that do not pay attention to the safety and comfort of traveling. This study was conducted to identify and analyze the physical quality of tourist attractions for elderly tourists which is associated with the development of the concept of sustainable tourism. The approach used in this study is a quantitative approach with data collection techniques using questionnaires. Data analysis in this study used the SmartPLS program, which was carried out in two stages, namely testing the outer model and inner model. The results obtained were that the influence of the quality of physical facilities on tourist satisfaction visiting tourist attractions has a positive and significant effect. While the application of the vitruvius theory moderates the influence of the quality of physical facilities on tourist satisfaction is unable to influence significantly. This study could be a reference for those who are interested in the same topic, especially about the relation between vitruvious theory and tourism.